Estudio de Fibrocementos reforzados con fibras vegetales como alternativa de refuerzo para las viviendas afectadas en el municipio de UNE en Cundinamarca (2021)
Fiber cements have been widely used since their invention, and despite their original use disadvantages, there is now the possibility of mixing them with natural fibers instead of asbestos, this combination offers environmentally friendly alternatives that, in addition, manage to achieve better resistance taking advantage of the chemical and physical properties of the material. With this in mind, this research focuses on a case study, where a series of houses in a town have been affected by mining activities, generating progressive and exponential wear that has put the structural integrity of the houses at risk. . The objective will be to elaborate a state of knowledge on elements based on natural fibers and cement, through the development of a theoretical framework that describes the properties of natural fibers, followed by a detailed analysis of tests on the same fibers, then The current state of the houses will be evaluated through a series of surveys and finally the results will be classified and interpreted, which will allow the conclusion How to improve the durability of the affected houses with a cement-based compound with vegetable fibers?